Properties of nanocomposite films with silicon nanoclusters and metal (Al) inclusions in the oxynitride matrix - Мурий Ярослав Юрійович (My University, 2024)
To date, a significant amount of research has been devoted to silicon-enriched SiOx films and SiO2(Si) nanocomposite films containing Si nanocrystals in an oxide matrix. The great scientific interest in such films is due to their charge capture and ability to emit light, which is very attractive, in particular, for use in Si-based nanoelectronics and optoelectronics, namely for non-volatile nanocrystalline and resistive memory, photodiodes, solar cells, field emission cathodes, etc. The formation of Si nanocrystals in the matrix of amorphous silicon oxynitride (SiOxNy) is a very promising approach to obtaining silicon-based nanocomposite structures. The ability to control the properties of SiOxNy by adjusting the amount and ratio of oxygen and nitrogen is the reason for the widespread use of this material for multilayer structures with a variable refractive index, waveguides, surface passivation layers, and medical implant coatings. The refractive index adjustment makes SiOxNy well suited for optical applications. The other class of oxide films, namely metal oxides, is represented by a wide variety of functional materials for many applications, including sensors, energy storage, catalysis, optoelectronics, photonics, etc. The introduction of semiconductor or metal nanoparticles into oxide and oxynitride matrices significantly affects their physical and chemical properties. Composite films containing metal nanoparticles in an oxide matrix demonstrate such interesting and important properties as negative magnetoresistance, enhancement of magneto-optical effects, and functionality as shields against electromagnetic radiation. The optical and electrical properties of such films can be significantly modified by realizing surface localized plasmon resonance in metal nanoparticles. The preparation and study of nanocomposite films containing both semiconductor and metal nanoparticles embedded in a dielectric matrix or semiconductor nanoparticles embedded in a combined semiconductor-metal oxide matrix is very promising. Such films can impart new properties that will be strongly dependent on the matrix structure, composition, natural defects, etc., controlling their electrical and optical properties, which is important for a wide class of applications. To use the latest nanocomposite films in micro- and nanoelectronics and optoelectronics, an important task is to study their electrophysical properties, in particular, to establish the mechanisms of electronic transport and frequency dependence of capacitance when they are used in metal-dielectric-semiconductor structures. Therefore, the development of technological processes for the production of nanocomposite films with silicon and aluminum inclusions, as well as the establishment of electronic transport mechanisms and capacitive properties is certainly relevant. The purpose of the dissertation is to develop technological processes for the production of SiAlzOxNy(Si) nanocomposite films with silicon and aluminum nanowires, to establish physical mechanisms of electronic transport and frequency dependencies of capacitance when used in metal-dielectric-semiconductor structures and the possibilities of using these films in electronics. The following scientific results were obtained in the course of the dissertation: - A technological process for the production of nanocomposite oxynitride films containing silicon and aluminum by ion-plasma sputtering was developed. - The mechanisms of electron transport through SiAlzOxNy(Si) nanocomposite films with silicon and aluminum naninclusions in a wide range of temperatures and electric fields have been established. - The parameters of electron traps involved in the electrical conductivity in the band gap of SiAlzOxNy(Si) nanocomposite films (concentration, energy position) have been determined. - The effect of the high-temperature annealing environment (argon, nitrogen) on the electrical conductivity of SiAlzOxNy(Si) nanocomposite films was determined. - It has been found that the addition of aluminum and the formation of an amorphous SiAlzOxNy matrix leads to an increase in the electrical conductivity of SiAlzOxNy(Si) nanocomposite films compared to SiOxNy(Si) films containing silicon nanoparticles in an oxynitride matrix. - The effect of decreasing electrical conductivity with increasing electric field intensity was revealed and a physical model was proposed to explain it. - The effect of negative capacitance in metal-dielectric-semiconductor structures with SiAlzOxNy(Si) nanocomposite film has been revealed and a physical model for its explanation has been proposed. The practical significance of the obtained results is that: - The developed and implemented technology for the production of SiAlzOxNy(Si) nanocomposite films by ion-plasma sputtering of silicon and aluminum targets makes it possible to obtain films of various compositions, which is the basis for their diverse use, including as materials for semiconductor devices, solar cells, thin films in electronics, coatings with good resistance to oxidation and corrosion, gates in transistors, optical films, dielectric materials, etc. - The discovered effect of negative capacitance can be used in the formation of film inductances in high-frequency integrated circuits. The introduction of the dissertation substantiates the relevance of the research topic, defines the object and subject of the study, according to which the aim and objectives of the work are formulated, indicates the research methods used, presents the scientific novelty of the results, their practical significance and forms of testing. The first section of the work presents an analytical review of the literature on the topic of the dissertation. Various methods of sputtering nanocomposite films, structural and electrical characteristics of nanocomposite films with metal inclusions, the effect of negative capacitance, and prospects for their use are analyzed. From the analysis of literature sources, the importance of the structural characteristics of nanocomposite films was determined. Based on this analysis, the research objectives and tasks of the dissertation are formulated. The second section describes the technology of producing SiAlzOxNy(Si) nanocomposite films by ion-plasma sputtering. The measurement techniques used to analyze the obtained structures are also described. In the third section, the structural and electrophysical properties of the nanocomposite films are determined. To characterize the structural properties, the films were studied by IR spectroscopy and spectral ellipsometry, and the results are analyzed. The results of studies of the electrical conductivity of SiOxNy(Si) and SiAlzOxNy(Si) nanocomposite films in a wide range of temperatures and electric field strengths and physical models to explain the properties and effects obtained are presented. To determine the mechanisms of electronic transport in the nanocomposite films, the current-voltage characteristics of the film were measured. In the fourth section, the results of the study of the capacitive properties of metal-dielectric-semiconductor structures with a SiAlzOxNy(Si) nanocomposite film containing Si nanoclusters embedded in an amorphous SiAlzOxNy matrix as a dielectric are presented. A physical model is proposed to explain the observed negative capacitance effect.

На сьогоднішній день значна кількість досліджень присвячена збагаченим кремнієм плівкам SiOx і нанокомпозитним плівкам SiO2(Si), що містять нанокристали Si в оксидній матриці. Великий науковий інтерес до таких плівок обумовлено захопленням ними заряду і здатністю випромінювати світло, що є дуже привабливим, зокрема, для застосування в наноелектроніці та оптоелектроніці на основі Si, а саме для енергонезалежної нанокристалічної та резистивної пам’яті, фотодіодів, сонячних елементів, польових емісійних катодів тощо. Формування нанокристалів Si в матриці аморфного оксинітриду кремнію (SiOxNy) є дуже перспективним підходом для отримання нанокомпозитних структур на основі кремнію. Можливість контролювати властивості SiOxNy шляхом регулювання кількості та співвідношення кисню та азоту є причиною широкого застосування цього матеріалу для багатошарових структур зі змінним показником заломлення, хвилеводів, поверхневих пасиваційних шарів та покриття медичних імплантатів. Регулювання показника заломлення робить SiOxNy добре придатним для оптичних застосувань. Інший клас оксидних плівок, а саме оксидів металів, представлений широкою різноманітністю функціональних матеріалів для багатьох застосувань, включаючи сенсорику, зберігання енергії, каталіз, оптоелектроніку, фотоніку тощо. Введення напівпровідникових або металевих наночастинок в оксидні та оксинітридні матриці істотно впливає на їх фізичні та хімічні властивості. Композитні плівки, що містять металеві наночастинки в оксидній матриці демонструють такі цікаві і важливі с точки зору практичного застосування властивості як негативний магнітоопір, посилення магнітооптичних ефектів та функціональність як захисних екранів від електромагнітного випромінювання. Оптичні та електричні властивості таких плівок можна суттєво модифікувати шляхом реалізації поверхневого локалізованого плазмонного резонансу у металевих наночастинках. Отримання та дослідження нанокомпозитних плівок, що містять як напівпровідникові, так і металеві наночастинки, вбудовані в діелектричну матрицю, або напівпровідникові наночастинки, вбудовані в комбіновану напівпровідник-метал оксидну матрицю є дуже перспективним. Такі плівки можуть надати нові властивості, які будуть сильно залежати від структури матриці, складу, природних дефектів тощо, керуючи їх електричними та оптичними властивостями, що є важливим для широкого класу застосувань. Для застосування новітніх нанокомпозитних плівок в мікро- та наноелектроніці і оптоелектроніці важливою задачею є дослідження їх електрофізичних властивостей, зокрема встановлення механізмів електронного транспорту та частотних залежностей ємності при їх використанні в структурах метал-діелектрик напівпровідник. Тому розроблення технологічних процесів отримання нанокомпозитних плівок з нановключеннями кремнію та алюмінію, встановлення механізмів електронного транспорту та ємнісних властивостей безумовно є актуальним. Метою дисертаційної роботи є розроблення технологічних процесів отримання нанокомпозитних плівок SiAlzOxNy(Si) з нановключеннями кремнію та алюмінію, встановлення фізичних механізмів електронного транспорту та частотних залежностей ємності при їх використанні в структурах метал- діелектрик напівпровідник і можливостей застосування даних плівок в електроніці. При виконанні дисертаційної роботи були одержані наступні наукові результати: - Розроблено технологічний процес отримання нанокомпозитної оксинітридної плівки з вмістом кремнію та алюмінію методом іонно-плазмового розпилення. - Встановлено механізми електронного транспорту через нанокомпозитні плівки SiAlzOxNy(Si) з нановключеннями кремнію та алюмінію в широкому діапазоні температур та електричних полів. - Визначені параметри електронних пасток, які приймають участь у електропровідності, в забороненій зоні нанокомпозитних плівок SiAlzOxNy(Si) (концентрація, енергетичне положення). - Встановлено вплив середовища високотемпературного відпалу (аргон, азот) на електропровідність нанокомпозитних плівок SiAlzOxNy(Si). - Встановлено, що додавання алюмінію і формування аморфної матриці SiAlzOxNy приводить до збільшення електропровідності нанокомпозитних плівок SiAlzOxNy(Si) в порівнянні з плівками SiOxNy(Si), що містять кремнієві нановключення в оксинітридній матриці. - Виявлено ефект зменшення електропровідності при збільшенні напруженості електричного поля та запропонована фізична модель для його пояснення. - Виявлено ефект від’ємної ємності в структурах метал-діелектрик- напівпровідник з нанокомпозитною плівкою SiAlzOxNy(Si) та запропонована фізична модель для його пояснення. Практичне значення одержаних результатів полягає в тому, що: - Розроблена та реалізована технологія отримання нанокомпозитних плівок SiAlzOxNy(Si) методом іонно-плазмового розпилення мішеней кремнію та алюмінію дає можливість отримувати плівки різного складу, що є основою для їх різноманітного використання, в тому числі в якості матеріалів для напівпровідникових пристроїв, сонячних батарей, тонких плівок в електроніці, покриттів з хорошою стійкістю до окислення і корозії, затворів у транзисторах, оптичних плівок, діелектричних матеріалів тощо. Виявлений ефект від’ємної ємності може бути використаний при формуванні плівкових індуктивностей в високочастотних інтегральних схемах та у якості діелектрика МДН транзисторів ІС наднизької потужності. У вступі дисертаційної роботи обґрунтовано актуальність теми дослідження, визначено об’єкт та предмет дослідження, відповідно до яких сформульовано мету та завдання роботи, вказано застосовані методи дослідження, представлено наукову новизну результатів роботи, їх практичне значення та форми апробації. У першому розділі роботи представлено аналітичний огляд літературних джерел за темою дисертації. Проаналізовані різноманітні методи напилення нанокомпозитних плівок, структурні та електричні характеристики нанокомпозитних плівок з включеннями металів, ефект від’ємної ємності та перспективи їхнього використання. З аналізу літературних джерел було показано суттєвий вплив структурних характеристик на властивості нанокомпозитних плівок. На основі проведеного аналізу сформульовано завдання дослідження та завдання дисертації. В другому розділі описуються технології отримання нанокомпозитних плівок SiAlzOxNy(Si) методом іонно-плазмового напилення. Також описані методики вимірювання, що застосовувалися для аналізу отриманих структур. В третьому розділі встановлюються структурні та електрофізичні властивості нанокомпозитних плівок. Для характеристики структурних властивостей було проведено дослідження плівки методами ІЧ-спектроскопії та спектральної еліпсометрії, наведений аналіз отриманих результатів. Наводяться результати досліджень електропровідності нанокомпозитних плівок SiOxNy(Si) та SiAlzOxNy(Si) в широкому діапазоні температур та напруженостей електричного поля і фізичні моделі для пояснення властивостей та отриманих ефектів. Для визначення механізмів електронного транспорту в нанокомпозитних плівках були виміряно вольт-амперні характеристики плівки в широкому діапазоні температур. В четвертому розділі представлено результати дослідження ємнісних властивостей структур метал-діелектрик-напівпровідник з нанокомпозитною плівкою SiAlzOxNy(Si), що містить нанокластери Si вбудовані в аморфну матрицю SiAlzOxNy, як діелектрик. Запропонована фізична модель для пояснення виявленого ефекту від’ємної ємності.
Властивості нанокомпозитних плівок з нанокластерами кремнію та включеннями металу (Al) в оксинітридній матриці
Keywords: нанокомпозитні плівки; оксинітридні матриці нанокристали Si; атоми Al; транспорт електронів; електронні пастки; ємність; nanocomposite films; oxynitride matrices; Si nanocrystals; Al atoms; electron transport; electron traps; capacitance